Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1107/s0021889803002012
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for setting up high-throughput nanolitre crystallization experiments. II. Crystallization results

Abstract: Harkiolaki, M et al. (2003) A procedure for setting up high-throughput nanolitre crystallization experiments. II. Crystallization results. Journal of Applied Crystallography, 36 (2). pp. 315-318.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Hampton Research sparse matrix & GRID screens were then set up (i.e., Crystal Screen I, Crystal Screen II, Crystal Screen Cryo, PEG/Ion, Natrix, MembFac, Index, SaltRX, PEG/LiCl Grid, NaCl Grid, PEG 6000 Grid, and A/S Grid). All crystallizations were performed at 293 K and set up as sitting‐drop vapor‐diffusion experiments, initially at 100‐nL droplet size using a Cartesian robot system,31 and later by hand for crystal optimization with 6‐μL droplet size. For crystals that grew from the screens, single frames of X‐ray data were collected in house, using a MAR345 image plate system on a Rigaku generator equipped with a Cu anode and Osmic multilayer optics to give Kα radiation (λ = 1.5418 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Hampton Research sparse matrix & GRID screens were then set up (i.e., Crystal Screen I, Crystal Screen II, Crystal Screen Cryo, PEG/Ion, Natrix, MembFac, Index, SaltRX, PEG/LiCl Grid, NaCl Grid, PEG 6000 Grid, and A/S Grid). All crystallizations were performed at 293 K and set up as sitting‐drop vapor‐diffusion experiments, initially at 100‐nL droplet size using a Cartesian robot system,31 and later by hand for crystal optimization with 6‐μL droplet size. For crystals that grew from the screens, single frames of X‐ray data were collected in house, using a MAR345 image plate system on a Rigaku generator equipped with a Cu anode and Osmic multilayer optics to give Kα radiation (λ = 1.5418 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Crystallization experiments were initially carried out at the Oxford Protein Production Facility (Brown et al. , 2003; Walter et al.…”
Section: Methodsmentioning
confidence: 99%
“…Key foundations for structural genomics included developments in macromolecular X-ray crystallography and NMR along with general systems for cloning and expression of proteins. In X-ray crystallography the increasing use of tunable synchrotron radiation in collecting anomalous diffraction data on protein crystals, the use of selenomethionine in crystallographic phase determination (68), automation of nanodroplet crystallization (11, 52), cryo-cooling techniques that reduced radiation damage to those crystals (30, 49), and automation of the structure determination process for macromolecular crystallography (47, 62) suggested that determining a protein structure once crystals were available would be increasingly straightforward. In the NMR field, the availability of cryo-probe high-field NMR devices (32), the development of multidimensional techniques for data acquisition (60), and the introduction of automated procedures for data analysis (8, 28, 43) similarly suggested that NMR structure determination was headed toward ever-higher throughput.…”
Section: Introductionmentioning
confidence: 99%